Antifibrotic effects of specific targeting of the 5-hydroxytryptamine 2B receptor (5-HT2BR) in murine models and ex vivo models of scleroderma skin - Trinh-Minh, Thuong; Tran-Manh, Cuong; Györfi, Andrea Hermina; Dickel, Nicholas; Liebel, Christoph; Zhou, Xiang; Wang, Jiucun; Kunz, Meik; Arozenius, Helena; Pettersson, Lars; Lindgren, Sam; Wenglén, Christina; et al. (Arthritis and Rheumatology, 2025)
Objective: Systemic sclerosis (SSc) is a connective tissue disease with fibrotic remodeling of the skin and various internal organs. SSc is associated with the highest case-specific mortality of all rheumatic autoimmune diseases with limited antifibrotic treatment options. Here, we evaluated the therapeutic effects of the highly selective 5-hydroxytryptamine 2B receptor (5-HT2BR) inhibitor AM1476. Methods: The antifibrotic effects of AM1476 were evaluated in the mouse models of bleomycin-induced pulmonary fibrosis in Tsk-1 mice and in mice with sclerodermatous chronic graft-versus-host disease. For further validation, the antifibrotic effects of AM1476 were analyzed in precision cut skin (PCS) slices from patients with SSc. Results: AM1476 demonstrated high selectivity for 5-HT2BR over more than 200 other receptors, including other 5-HT receptors in vitro. AM1476 reduced accumulation of hydroxyproline and fibrotic tissue remodeling of skin and/or lungs in all three mouse models at well-tolerated doses with a comparable efficacy to that of nintedanib. In PCS of SSc skin, treatment with AM1476 reduced the expression of SSc-specific signature genes. AM1476 demonstrated more pronounced regulation of terms related to fibroblast activation and fibrotic remodeling than mycophenolate mofetil. Conclusion: We describe AM1476 as a highly selective inhibitor of 5-HT2BR. Treatment with AM1476 ameliorated fibrosis in three mouse models of SSc and normalized the expression of fibrosis-related genes directly in SSc skin. Because AM1476 also demonstrated good tolerability in a phase 1 trial, further clinical trials with AM1476 are currently in the planning stage.
CRIS-Team Scopus Importer:2025-05-30